Implementasi Pemodelan Matematika di Sekolah Dasar - Prasetyo, Teguh (Universitas Muhammadiyah Magelang, 2017)
Innovative and creative learning models are a necessity in creating effective learning in the classroom. Therefore, a trial of a learning model is required. Quasi experimental research was conducted in class V SDN Kaumpandak 02 Bogor Regency which has a population of 68 students. The implementation of this research was conducted in the even semester of the academic year 2016/2017. The instruments of data collection were taken using tests and observations. Based on inferential analysis test result of applying sig value of mathematical modeling and control class using learning which is used by teacher have value sig 0,00 <0,05, then H0 is rejected. So between the experimental class and the control class there is an influence of significance on the learning outcomes of mathematics. Between the two have a difference level on the mean difference that is in the experimental class 56.61 and and the control class 55.14. Thus the use of mathematical modeling in the experimental class has a positive effect on the students' mathematics learning outcomes.